2021
DOI: 10.3389/fcvm.2021.632302
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric vs. Inferior Vena Cava–Based Estimation of Right Atrial Pressure

Abstract: Background: Right atrial pressure (RAP) can be estimated by echocardiography from inferior vena cava diameter and collapsibility (eRAPIVC), tricuspid E/e′ ratio (eRAPE/e′), or hepatic vein flow (eRAPHV). The mean of these estimates (eRAPmean) might be more accurate than single assessments.Methods and Results: eRAPIVC, eRAPE/e′, eRAPHV (categorized in 5, 10, 15, or 20 mmHg), eRAPmean (continuous values) and invasive RAP (iRAP) were obtained in 43 consecutive patients undergoing right heart catheterization [medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…1 The American Society of Echocardiography supports the use of ultrasound assessment of IVC maximum diameter (IVC max ) and IVC collapsibility index (CI) with respiration to estimate right atrial pressure (RAP), 3,4 with recent validation. 5 IVC CI measurements have reasonable sensitivity (84%-96%) and specificity (37%-93%) for diagnosis of congestive heart failure, 6 and may help guide diuresis and heart failure therapy to improve patient outcomes. 7 The goal of volume management is to improve cardiac output by optimizing relative intravascular volume.…”
Section: Introductionmentioning
confidence: 99%
“…1 The American Society of Echocardiography supports the use of ultrasound assessment of IVC maximum diameter (IVC max ) and IVC collapsibility index (CI) with respiration to estimate right atrial pressure (RAP), 3,4 with recent validation. 5 IVC CI measurements have reasonable sensitivity (84%-96%) and specificity (37%-93%) for diagnosis of congestive heart failure, 6 and may help guide diuresis and heart failure therapy to improve patient outcomes. 7 The goal of volume management is to improve cardiac output by optimizing relative intravascular volume.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there was no significant difference in IVC diameter between the two groups. The IVC diameter reflects venous return and right atrial pressure [ 9 ], and the changes can be good indicators of fluid status, especially in a chronological comparison of the same case. However, the IVC diameter is affected by multiple comorbidities including congestive heart failure, valvular diseases, arrhythmias, and lung diseases [ 10 ]; hence, a comprehensive interpretation is essential along with other parameters and pathological conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies showed only moderate reproducibility [ 55 ] of hepatic vein Doppler to predict RAP, and recently, some authors failed to reproduce the proposed eRAP index in a cohort of patients who underwent RHC. They conclude that the multiparametric eRAP index does not provide an advantage over guidelines suggested for RAP assessment, despite being more complex and time consuming [ 56 ]. In the field of advanced heart failure, it is of paramount importance to stress that our tool is able to predict right heart chambers congestion only, on the other hands, there are several echocardiographic techniques to predict left ventricular end diastolic pressure, which is another important parameter to know how to correctly manage such advanced patients [ 1 ].…”
Section: Rap In Advanced Heart Failure and Pulmonary Hypertensionmentioning
confidence: 99%